Pendampingan Akuntansi untuk Mendukung Efektifitas Pembayaran PPh 21 pada Koperasi Kredit Kosayu - Endah Puspitosarie; Indah Dewi Nurhayati; Zainuddin Zainuddin (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service activity was carried out as an effort to improve the effectiveness of reporting and withholding of Income Tax (PPh) Article 21 at the Kosayu Credit Cooperative through accounting-based technical assistance. The main problem identified during the Field Work Practice (PKL) activity was the potential for tax overpayments caused by inaccurate estimates of employee annual income and limitations of the payroll system used by the cooperative. To address these problems, the implementation team implemented several methods, namely direct observation of the tax administration process, technical training for related staff, tax calculation simulations based on actual data, and evaluation of the existing tax recording and reporting system. The results of the activity showed that although the cooperative had used the Average Effective Rate (TER) method for withholding PPh 21, its implementation was still not optimal because it was not supported by an integrated information system and a regularly updated employee database. This resulted in inaccuracies in tax calculations and withholding. Therefore, this assistance recommended several improvements, including updating the payroll system, improving employee data, integrating the digital tax reporting system, and increasing the capacity of the cooperative's human resources through ongoing training related to tax regulations. In addition to having a direct impact on the efficiency of cooperative tax management, this program also provides contextual learning benefits for students in linking tax accounting theory with real conditions in the field.